2016
DOI: 10.1111/jphp.12654
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 (ET-1) stimulates carboxy terminal Smad2 phosphorylation in vascular endothelial cells by a mechanism dependent on ET receptors and de novo protein synthesis

Abstract: In BAECs, ET-1 via the ETB receptor is involved in transactivation of the TβRI. The transactivation-dependent response is dependent upon de novo protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…ET-1 is a 21-amino-acid peptide with a powerful vasoconstrictor effect in conductive and resistive arteries [41]. The balance between ET-1 and NO provides an endothelial barrier to lipoprotein influx and macrophage recruitment, stimulating cell proliferation and contributing to endothelial dysfunction.…”
Section: Endothelin-1mentioning
confidence: 99%
“…ET-1 is a 21-amino-acid peptide with a powerful vasoconstrictor effect in conductive and resistive arteries [41]. The balance between ET-1 and NO provides an endothelial barrier to lipoprotein influx and macrophage recruitment, stimulating cell proliferation and contributing to endothelial dysfunction.…”
Section: Endothelin-1mentioning
confidence: 99%
“…It was originally discovered that Ang II activated the PTK receptors in the fibroblast cells in a process that was termed transactivation . Later, other studies showed that various GPCR agonists such as ET‐1 and thrombin are able to activate other receptors such as PTKR and S/TKR in VSMCs . In 2013, Burch et al .…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that thrombin can mediate the phosphorylation of Smad2C via cytoskeleton/ROCK/integrin axis, leading to activation of the TβRI and phosphorylation of Smad2C (Ser465/467); thrombin via transactivation of these two kinase receptors increases the synthesis of proteoglycans in VSMCs. Our group showed that ET‐1 phosphorylated C‐terminal Smad2 in endothelial cells via transactivation of TβRI but downstream mediators that involved in TβRI transactivation remained unknown …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the original observations, this paradigm has recently been expanded to include the transactivation of serine/threonine kinase receptors (S/TKR) notably transforming growth factor (TGF)-β type 1 receptor (TGFBR1). In human vascular smooth muscle cells (VSMCs), treatment with thrombin (12,13) or endothelin-1 (ET-1) (14,15) stimulates carboxy terminal phosphorylation of the transcription factor Smad2. This response was blocked by the TGFBR1 antagonist, SB431542, indicating that the response arises from GPCR transactivation of TGFBR1 (13,14,16,17).…”
Section: Introductionmentioning
confidence: 99%